2013
DOI: 10.1097/01.naj.0000429756.00008.ca
|View full text |Cite
|
Sign up to set email alerts
|

Original Research

Abstract: This review provides nurses and other clinicians with a synthesis of research on telephone follow-up in patients after myocardial revascularization. Of the seven studies analyzed, five showed evidence of some benefit from telephone follow-up. Their findings support the use of telephone follow-up to periodically assess patient knowledge, discuss patient concerns and offer ways to address them, monitor mood symptoms and anxiety levels, and encourage behavioral and lifestyle changes. Although any telephone follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Telephone calls are probably more sustainable than home visits in these regards since they are easily organised and accessible involving low technology [ 4 ]. The time spent on calls in various studies ranged from 15 to 60 min [ 27 ] which concurs with our findings. The length of intervention is reasonable, and without the involvement of traveling time, which in turn saves cost.…”
Section: Discussionsupporting
confidence: 92%
“…Telephone calls are probably more sustainable than home visits in these regards since they are easily organised and accessible involving low technology [ 4 ]. The time spent on calls in various studies ranged from 15 to 60 min [ 27 ] which concurs with our findings. The length of intervention is reasonable, and without the involvement of traveling time, which in turn saves cost.…”
Section: Discussionsupporting
confidence: 92%
“…It needs several improvements of educational strategies in order to maintain participants' knowledge and behaviors regarding foot care. One systematic review reported that the followup strategies, such as a telephone call were effective and feasible to assess knowledge, discuss the patients' concerns, and encourage lifestyle and behavioral changes [19].…”
Section: E Discussionmentioning
confidence: 99%
“…Therefore, it is important to manage risk factors after the treatment to prevent cardiac symptoms and coronary artery stenosis. Nearly one million CABGs are performed in the world each year (1,3,10).…”
Section: Introductionmentioning
confidence: 99%